Evaluation on The Use of Antibiotics for Pneumonia Patients - Nada Zavira; Abdul Kadir Jaelani; Fauna Herawati; Rika Yulia (poltekkes kemenkes mataram, 2021)
Pneumonia is an acute infectious disease that attacks lung tissue (alveoli) which can be caused by viral, bacterial, or fungal infections. Pneumonia is one of the diseases that have the highest death risk in Indonesia. The first line of treatment for pneumonia is antibiotic therapy. Inappropriate use of antibiotics will increase the possibility of antibiotic resistance. Antimicrobial Control Program (PPRA) is a health surveillance to control the use of antibiotics where the indicator of success is seen from the improvement in the quantity and quality of antibiotic use. Antibiotic control that can be performed is evaluating the use of antibiotics quantitatively and evaluating the suitability of antibiotics. The purpose of this study was to determine the quantity of antibiotic use with the DDD/100 patient-days unit and the suitability of the use of antibiotics based on PPAB. This study was observational, the data were taken retrospectively and analyzed descriptively. The research material used medical record data for pneumonia patients from January to June 2020 at RSUD Bangil. There were 91 research samples obtained by purposive sampling that met the inclusion and exclusion criteria. The data were analyzed quantitatively using the DDD/100 patient-days unit and 90% DU, and the suitability of antibiotics was analyzed using five indicators of the right indication, the right route, the right dose, the right interval, and the right time of administration. The results showed the use of antibiotics with a total value of DDD/100 patient-days of 78.13 DDD/100 patient-days with the highest value on moxifloxacin (39.28 DDD/100 patient-days). Antibiotics included in the 90% segment that need to be controlled are parenteral moxifloxacin (50.27%), ceftriaxone (23.34%), azithromycin (6.83%), oral moxifloxacin (4.62%), and levofloxacin (3.85%). The suitability of antibiotics based on PPAB RSUD Bangil 2019 showed the right indication (51.65%), right route (100%), right dose (87.23%), right interval (48.93%), and right time of administration (10.64). %).